Power BI masterclass : beginners to advanced - We, Daniel (Packt Publishing, 2018)
"Companies are constantly searching for ways to make better and faster decisions. Therefore they rely heavily on data. Data-driven decision making is the key to success for any business in the world of tomorrow. Because of that companies are constantly searching for skilled employees and freelancers with the necessary capabilities to help with analyzing data and creating valuable highly profitable insights. This will be the key advantage to succeed in business. MS Power BI is an advanced yet easy to get started self-service business analytics/business intelligence solution provided by Microsoft and it's currently in very hot demand. Daniel can confirm that companies will actively be searching for you if you master Power BI. And you can be part of this future! There is no coding required! Power BI allows you to do that but it's not necessary."--Resource description page